Limit Theorems for Bipower Variation in Financial Econometrics. - Barndorff-Nielsen, O; Graversen, S; Jacod, J; Shephard, N (Cambridge University Press, 2006)
In this paper we provide an asymptotic analysis of generalized bipower measures of the variation of price processes in financial economics. These measures encompass the usual quadratic variation, power variation, and bipower variations that have been highlighted in recent years in financial econometrics. The analysis is carried out under some rather general Brownian semimartingale assumptions, which allow for standard leverage effects.